Csr1/Zap1 Maintains Zinc Homeostasis and Influences Virulence in Candida dubliniensis but Is Not Coupled to Morphogenesis - Böttcher, Bettina (Eukaryot Cell, 2015)
The supply and intracellular homeostasis of trace metals are essential for every living organism. Therefore, the struggle for micronutrients between a pathogen and its host is an important determinant in the infection process. In this work, we focus on the acquisition of zinc by Candida dubliniensis, an emerging pathogen closely related to Candida albicans. We show that the transcription factor Csr1 is essential for C. dubliniensis to regulate zinc uptake mechanisms under zinc limitation: it governs the expression of the zinc transporter genes ZRT1, ZRT2, and ZRT3 and of the zincophore gene PRA1. Exclusively, artificial overexpression of ZRT2 partially rescued the growth defect of a csr1Δ/Δ mutant in a zinc-restricted environment. Importantly, we found that, in contrast to what is seen in C. albicans, Csr1 (also called Zap1) is not a major regulator of dimorphism in C. dubliniensis. However, although a csr1Δ/Δ strain showed normal germ tube formation, we detected a clear attenuation in virulence using an embryonated chicken egg infection model. We conclude that, unlike in C. albicans, Csr1 seems to be a virulence factor of C. dubliniensis that is not coupled to filamentation but is strongly linked to zinc acquisition during pathogenesis.